(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The relevance of the problem of congenital viral infectious diseases is due to their wide prevalence, high frequency of latent and subclinical forms, as well as significant economic damage associated with the costs of diagnosis, treatment and rehabilitation [17,18,19,20].